Medicine Shortages: From Assumption to Evidence to Action - A Proposal for Using the FMD Data Repositories for Shortages Monitoring - Bouvy, François; Rotaru, Mihai (Frontiers in Medicine, 2021)
Medicine shortages may negatively impact patient care and the patient experience. Shortages should be a priority of industry, supply chain stakeholders and national competent authorities, and deserve more than empathy or “lip-service” but serious engagement and action. Under the overarching principle that without correct measurements in place there cannot be any improvement in overall performance (1), stakeholders in the pharmaceutical supply chain, notably pharmaceutical manufacturers have made the call for all relevant sources of information to be used in order to provide additional intelligence about the root causes and drivers of shortages, including the identification of bottlenecks in the supply chain. This paper outlines a proposal for using the data stored in the interoperable network of national repositories being set up in the context of the Falsified Medicines Directive (Directive 2011/62/EU) and its Delegated Regulation 2016/161/EU on safety features for providing additional intelligence in monitoring shortages. The paper analyses the potential feasibility and readiness of using this data for monitoring shortages as well as the strengths and weaknesses of the approach. We explore also what are some of the other complementary data sources that could be analyzed in conjunction with the data in the repository system to sharpen the overall analysis. Lastly, we provide a theoretical but concrete use case for using the abovementioned data for better informing decisions to prevent and mitigate shortages. In doing so, we explain the interlink between patient needs at country level, demand from economic actors, intra-EU parallel trade and manufacturer-imposed supply quotas and propose a mechanism for collaboration between national competent authorities and supply chain stakeholders for early detection and action to prevent medicine shortages from occurring.